Value of Clinical Signs in Identifying Patients with Scans without Evidence of Dopaminergic Deficit (SWEDD) - Suwijn, Sven R. (J Parkinsons Dis, 2020)
BACKGROUND: In clinical trials that recruited patients with early Parkinson’s disease (PD), 4–15% of the participants with a clinical diagnosis of PD had normal dopamine transporter single photon emission computed tomography (DAT SPECT) scans, also called “scans without evidence of dopaminergic deficit” (SWEDD). OBJECTIVE: To investigate in patients with a clinical diagnosis of PD, if specific clinical features are useful to distinguish patients with nigrostriatal degeneration from those that have no nigrostriatal degeneration. METHODS: We performed a diagnostic test accuracy study. Patients that participated in the Levodopa in Early Parkinson’s disease trial, a clinical trial in patients with early PD, were asked to participate if they had not undergone DAT SPECT imaging earlier. The index tests were specific clinical features that were videotaped. A panel of six neurologists in training (NT), six general neurologists (GN), and six movement disorders experts (MDE) received a batch of ten videos consisting of all SWEDD subjects and a random sample of patients with abnormal DAT SPECT scans. The raters analyzed the videos for presence of specific signs and if they suspected the patient to have SWEDD. The reference test was visually assessed DAT SPECT imaging. RESULTS: Of a total of 87 participants, three subjects were SWEDDs (3.4%). The overall intraclass correlation coefficient (ICC) of the Parkinsonian signs was poor to moderate with ICCs ranging from 0.14 to 0.67. NT correctly identified 50.0% of the SWEDD subjects, GN 33.3%, and MDE 66.7%. CONCLUSION: Our study suggests that the selected videotaped clinical features cannot reliably distinguish patients with a clinical diagnosis of PD and an abnormal DAT SPECT from patients with clinical PD and a SWEDD.